Teachers' attitudes towards the implementation of the strategy of blended learning in public secondary schools Field study in schools in Latakia province - أحمد , لانا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The aim of this research is to identify the trends of teachers towards the application of the strategy of blended learning in public secondary schools in Latakia province, and in order to achieve the objectives of the research was used descriptive analytical method through the design of a questionnaire consisting of (35) items distributed over three axes, while the sample of the research It consisted of 348 teachers, and the most important findings of the research were: The degree of teacher approval of the benefits of the blended learning strategy was high, as well as the degree of interest in this strategy, while the possibility of its application in public secondary schools was medium. - There are no statistically significant differences in the opinions of teachers about the benefits of the strategy blended learning according to the variable nature of the subject (scientific, literary), while there have been differences in the degree of interest and applicability in favour of teachers who teach scientific subjects. - There are no statistically significant differences in teachers' opinions on the benefits of a strategy of blended learning according to the variable location of the school (city, countryside), while there have been differences in the degree of interest and applicability in favour of teachers who teach in city schools.